2015
DOI: 10.1038/nchembio.1736
|View full text |Cite
|
Sign up to set email alerts
|

Modular construction of mammalian gene circuits using TALE transcriptional repressors

Abstract: An important goal of synthetic biology is the rational design and predictable implementation of synthetic gene circuits using standardized and interchangeable parts. However, engineering of complex circuits in mammalian cells is currently limited by the availability of well-characterized and orthogonal transcriptional repressors. Here, we introduce a library of 26 reversible transcription activator-like effector repressors (TALERs) that bind newly designed hybrid promoters and exert transcriptional repression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
99
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(101 citation statements)
references
References 50 publications
1
99
0
1
Order By: Relevance
“…Localizing a DBD without an effector domain to promoter regions or downstream of the transcription start site can silence gene expression 32, 37, 68, 69 . In these strategies, repression is caused by steric interference of transcription factor binding and RNA polymerase elongation 69 .…”
Section: Site-specific Epigenome Editingmentioning
confidence: 99%
“…Localizing a DBD without an effector domain to promoter regions or downstream of the transcription start site can silence gene expression 32, 37, 68, 69 . In these strategies, repression is caused by steric interference of transcription factor binding and RNA polymerase elongation 69 .…”
Section: Site-specific Epigenome Editingmentioning
confidence: 99%
“…In addition, Dr. Wang demonstrated that there was a non-reciprocal competition effect between partial and perfect complementary targets caused by different miRNA loss rate in these two types of regulations. In another talk, Dr. Zhen Xie (Tsinghua University, China) demonstrated a library of reversible transcription activator-like effector repressors (TALERs) that bound designed hybrid promoters and exerted transcriptional repression through steric hindrance of key transcriptional initiation elements [24]. Dr. Xie showed that the performance of modularly assembled TALER cascade and switch circuits could be quantitatively predicted by using the input-output transfer functions of individual TALER constituents, indicating that this TALER library could be a valuable toolkit to facilitate modular engineering of synthetic circuits.…”
Section: Pathways and Network In Actionmentioning
confidence: 99%
“…In certain circumstances, limited durations or transmission of artificial manipulation may be preferable. Furthermore, the versatility and multiplex capacity of these genome engineering tools combined with the recent advances in synthetic eukaryotic genetic circuit designs (Khalil et al 2012;Slusarczyk et al 2012;Esvelt et al 2013;Farzadfard et al 2013;Daringer et al 2014;Kabadi et al 2014;Kiani et al 2014;Nielsen and Voigt 2014;Nissim et al 2014;O'Connell et al 2014;Li et al 2015b;Zalatan et al 2015) may lead to the next generation of cell therapies (Fig. 3B).…”
Section: Genome Engineering To Model Disease and Develop Therapeuticsmentioning
confidence: 99%